The Impact Of Religiosity And Service Quality On The Saving Decisions Of Tabaru’ Account Holders At KSPPS BMT Peta Malang Branch With Interest As A Mediating Variable - Masriyah, Siti (ITB AAS INDONESIA Surakarta, 2024)
This study aims to determine the impact of religiosity and service quality on the saving decisions of tabaru' account holders at KSPPS BMT PETA Malang Branch, with interest serving as a mediating variable. The research employs a quantitative approach. The population in this study comprises tabaru' account holders. Sampling was conducted using purposive sampling. Data for this study were collected using primary data from questionnaires. The analysis method employed is path analysis using SmartPLS 4. The results of this study indicate that religiosity and service quality variables have a significant impact on saving decisions. Additionally, religiosity and service quality have a significant impact on interest, and interest has a significant impact on saving decisions. Furthermore, interest can mediate the relationship between religiosity and service quality with saving decisions. This study demonstrates that religiosity and service quality significantly affect saving decisions through interest as a mediating variable.